Penyelesaian Sengketa Pemeliharaan Anak (Alimentasi Akibat Pasca Perceraian) Studi Kasus Pengadilan Agama Gorontalo - Riana Hasyim; Muthia Cherawaty Thalib; Sri Nanang Kamba (Universitas Sains dan Teknologi Komputer, 2023)
This research aims to find out how child maintenance disputes are resolved. In addition, to examine the resolution of child maintenance disputes. In this research, researchers used empirical research methods. This research method provides an overview of existing facts (empirical) as well as an accurate analysis of applicable laws and regulations in connection with legal theories and practice of implementing existing legal rules.The results of this research show that in giving a decision regarding child custody there are several basic considerations for the judge, one of which is based on the complications of Islamic law in article 150 part (a) which states that the maintenance of a child who is not yet 12 years old is the right of the mother, however, if the mother is negligent in taking care of the child or in other words not being responsible for the child's custody, the child's custody can be given to the father. Apart from that, custody also falls to the mother because the child's father does not have a permanent job or because of this he lacks economic means.